Design and development of single-qubit ion trap on glass and Si substrates with RF analysis and performance benchmarking - Apriyana, Anak Agung Alit (2021)
This article presents the design and development of surface electrode ion traps on glass and Si substrates and their radio frequency (RF) characterizations and performance benchmarking. In this case, the ion trap on glass shows superior performances in all necessary criteria. In terms of RF characterizations, ion traps on glass have a Q factor of greater than 900. This is significantly higher than the Q factor of its silicon counterparts, which are around 20-300. Such a high Q factor results in power spectral density (PSD) of greater than 10 W/MHz. On the other hand, ion traps on silicon produce PSD values of lower than 3 W/MHz. In terms of RF performance, the ion trap on glass shows insertion loss lower than 0.2 dB at 60 MHz. This is more superior to insertion loss values of ion traps on silicon, which are around 1-4 dB. The ion-traps metallization is developed using three metallization layers (0.1- mu textm Ti barrier layer, 2.5-3.7- mu textm Cu, and 0.3- mu textm Au) on top of the dielectric. The on-chip resonance condition can be maintained upon packaging integration. The laser optical setup for ion trapping is verified to capture a single 88Sr+ ion.